Renovando as letras: o movimento modernista no Ceará entre tensões e contradições (1923-1931) - Sousa, Alexandre Vidal de (2018)
The present work aims to analyze the modernist movement in the state of Ceará, initiating in the year of 1923, period in which the movement is criticized, even before of arising modernists in Ceará. The research dwells on until 1927, year of publication of the opening book of the movement in Ceará, entitled O Canto Novo da Raça, ending in 1931, when it is published the independent paper Cipó de Fogo. The aim is to realize the process of participation and inclusion of interested local writers on proposals of esthetic and cultural renovation, and, in particular, on fighting against artistic “old models” connected to an academic tradition. The main sources presented in order to analyze the issues are productions in books, magazines, manifestos, letters and primarily newspapers, in which they were produced to expose ideas. The work methodology takes into account the features of the literary system described by Antonio Candido – authors, works and audience – concerning the formation effort of a local literary level, and it is based on the concept of literary field of Bourdieu, in order to explain the conflicts and contests among generations and scholars groups. The work still aims to provide a better understanding about how it was possible to think of a modernist project and, precisely, in which social conditions it was developed in Ceará. In general terms, it was realized that, as well as in all over the country, the modernist movement, in Ceará, was not a homogenous movement; it was characterized by the plurality and diversity of ideas. The esthetic productions of that age embodied the esthetic changes wished by modernists and revealed, not only their main ideas, however their tensions and contradictions. These ones allowed us to comprehend the text and the context, as well as the relationship between them.